NGHIÊN CỨU HẤP PHỤ ZN(II) DẠNG CỘT CỦA HẠT VẬT LIỆU BVNQ CHẾ TẠO TỪ ĐUÔI THẢI QUẶNG BAUXIT BẢO LỘC - Hùng, Doãn Đình; Minh, Nguyễn Trung (Vietnam Journal of Earth Sciences, 2012)
Study of Zn(II) sorption on Bao Loc modified-granular bauxite mining tail by column experiment In this study, we present the results of sorption capacity of Zn(II) on BVNQ (Bao Loc modified-granular bauxite mining tail - Basalt Phuoc Long, Vietam). Sorption of Zn(II) on BVNQ were identified by using column sorption experiments, X-ray fluorescence (XRF), X-ray diffraction (XRD), surface area (BET) and Energy Dispersive X-ray Spectroscopy/Field Emission Scanning Electron Microscope (EDS/FESEM). XRF result showed that Al2O3 and Fe2O3 are major components for Bao Loc bauxite mining tail. XRD result indicated that BVNQ from bauxite mining tail is composed of goethite, hematite, illite, kaolinite,… minerals, which are effective for heavy metal removal in environments. Also, BVNQ have high BET surface area. Results of sorption of Zn(II) on BVNQ (0.05 kg) by column experiment showed that the sorption decrease with increasing time during the sorption experiment (as well as increasing volume of output solution), ratio of output solution concentration (Ce) per input solution concentration (C0) is Ce/C0 = 0.15-0.7 (sorption from 30 to 85%) with volume of output Zn(II) solution is 63L, after 23 days. pH of output solution decrease with increasing sorption time from 10.2 to 7.0. Sorption capacity of Zn(II) on BVNQ (5700 mg/kg) by column experiment is much more higher than sorption capacity (894.88 mg/kg) by batch experiment.